Our culture of pandering - Simon, Paul, 1928-2003 (Southern Illinois University Press, 2003)
"In Our Culture of Pandering, former U.S. Senator Paul Simon interrogates the arenas of politics, media, religion, and education to decry the compromising practices that confuse public service with profit making and popularity as he calls needed attention to leadership failures that undercut the best interests of the nation to appease a powerful elite."